1988
DOI: 10.1161/01.cir.77.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Dilation of normal and constriction of atherosclerotic coronary arteries caused by the cold pressor test.

Abstract: Increased vascular constriction has been observed at the site of atherosclerotic lesions, suggesting an association between atherosclerosis and altered vascular tone. While atherosclerosis may increase sensitivity to exogenous vasoconstrictors, little is known about the response of normal and atherosclerotic coronary arteries to an exogenous stimulus that excites the sympathetic nervous system. Therefore, we studied the response to cold pressor test (CPT) using quantitative angiography and Doppler flow velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
231
3
9

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(262 citation statements)
references
References 42 publications
19
231
3
9
Order By: Relevance
“…With dysfunctional endothelium, the release of nitric oxide by the endothelium is significantly compromised, which can result in abnormal vasomotion during exercise, pacing, or exposure to cold. 44 Application of acetylcholine-in healthy arteries a powerful vasodilator because of the release of nitric oxide from the endothelium-can lead to paradoxical vasoconstriction, as constrictor effects of muscarinic receptors on vascular smooth muscles predominate over endothelial nitric oxide release. 45 The study by Halcox et al 43 demonstrated that especially coronary arterial segments that contracted after application of acetylcholine, denoting endothelial dysfunction, dilated after application of acetylcholine combined with sildenafil treatment, suggesting that the inhibition of cGMP breakdown by sildenafil could at least in part compensate for reduced nitric oxide-related cGMP production due to endothelial dysfunction.…”
Section: Effects Of Pde 5 Inhibition On Coronary Circulationmentioning
confidence: 99%
“…With dysfunctional endothelium, the release of nitric oxide by the endothelium is significantly compromised, which can result in abnormal vasomotion during exercise, pacing, or exposure to cold. 44 Application of acetylcholine-in healthy arteries a powerful vasodilator because of the release of nitric oxide from the endothelium-can lead to paradoxical vasoconstriction, as constrictor effects of muscarinic receptors on vascular smooth muscles predominate over endothelial nitric oxide release. 45 The study by Halcox et al 43 demonstrated that especially coronary arterial segments that contracted after application of acetylcholine, denoting endothelial dysfunction, dilated after application of acetylcholine combined with sildenafil treatment, suggesting that the inhibition of cGMP breakdown by sildenafil could at least in part compensate for reduced nitric oxide-related cGMP production due to endothelial dysfunction.…”
Section: Effects Of Pde 5 Inhibition On Coronary Circulationmentioning
confidence: 99%
“…Elevated LDL-C reduces dilation that normally occurs, 36 and visible lesions reduce or even reverse dilation. 37 Vascular remodeling and chronic EDRF effects, which appear closely related to lesion progression and regression, have been observed in several lipid-lowering trials. Early indication of lesion remodeling came from the Lifestyle Heart Trial, in which favorable changes in the entrance and exit shape of lesions were reported in the intensively treated group.…”
Section: Endothelium-derived Relaxing Factor and Vascular Remodelingmentioning
confidence: 99%
“…These changes result in an increase of coronary blood flow and dilation of coronary arteries. 18 On the contrary, CPT can induce blunt vasodilatation or paradoxical vasoconstriction in patients with coronary endothelial dysfunction. 18 The vasomotor dysfunction to CPT is observed very early in the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…18 On the contrary, CPT can induce blunt vasodilatation or paradoxical vasoconstriction in patients with coronary endothelial dysfunction. 18 The vasomotor dysfunction to CPT is observed very early in the development of atherosclerosis. 19 However, it is not completely defined that change of coronary flow velocity of the distal LAD during CPT with TTE is related to actual coronary endothelial function.…”
Section: Discussionmentioning
confidence: 99%